Dual-polarimetric terraSAR-X SAR data for target at sea observation - Velotto, Domenico; Nunziata, Ferdinando; Migliaccio, Maurizio; Lehner, Susanne (IEEE Geoscience and Remote Sensing Letters, 2013)
A physical dual-polarimetric model to observe man-made metallic targets at sea in dual-polarimetric coherent X-band synthetic aperture radar (SAR) data is proposed. The model exploits the intrinsic different symmetry properties of man-made targets and sea surface and is tested over actual StripMap TerraSAR-X HH-HV and VV-VH dual-polarimetric SAR data and colocated ground truth measurements. Then, an operational physically based filter to observe targets at sea is proposed. The filter is very attractive in terms of both detection performances and processing time. A typical SAR scene is processed in seconds by a conventional PC processor. © 2004-2012 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: PolSAR; ship detection; symmetry